2008
DOI: 10.1007/s11104-008-9853-4
|View full text |Cite
|
Sign up to set email alerts
|

White lupin leads to increased maize yield through a soil fertility-independent mechanism: a new candidate for fighting Striga hermonthica infestation?

Abstract: Nitrogen (N)-deficiency and lack of phosphorus (P) availability are major constraints to maize yields in Western Kenya. In a two-season field study in the lake Victoria basin, we tested the capacity of white lupin (Lupinus albus (L.), cv. Ultra), as a nitrogenfixing crop with a highly efficient P-acquisition capacity, to increase maize yields when used as a companion or cover crop, or as a source of organic matter. Each experiment was performed on three different fields (Vertisols) differing in N/P availabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The two field sites (particularly Kyela) are characterized by poor soil fertility, caused by continuous crop production without nutrient replenishment by appropriate fertilizer applications. Confirming our own soil fertility assessments, soils in Kyela are characterized by 0.16% N and around 5 ppm of available P ( Mghase et al, 2010 ) while soils in Mbita have been reported to have 0.09–0.12% N and 6.3–13.3 ppm available P ( Weisskopf et al, 2009 ). This relative poor soil fertility has certainly negatively affected crop performance, in particular in Kyela.…”
Section: Discussionsupporting
confidence: 66%
“…The two field sites (particularly Kyela) are characterized by poor soil fertility, caused by continuous crop production without nutrient replenishment by appropriate fertilizer applications. Confirming our own soil fertility assessments, soils in Kyela are characterized by 0.16% N and around 5 ppm of available P ( Mghase et al, 2010 ) while soils in Mbita have been reported to have 0.09–0.12% N and 6.3–13.3 ppm available P ( Weisskopf et al, 2009 ). This relative poor soil fertility has certainly negatively affected crop performance, in particular in Kyela.…”
Section: Discussionsupporting
confidence: 66%
“…Lupins also strongly inhibit germination of the seeds of the parasitic weed, Striga hermonthica , thus increasing the yield of maize ( Zea mays ) when used as a cover crop (Weisskopf et al . ). Similarly, we found evidence of inhibition of mycorrhizal sporulation near cluster roots of Banksia prionotes (Proteaceae; F.P.…”
Section: Interactions Between Mycorrhizal and Non‐mycorrhizal Speciesmentioning
confidence: 97%
“…The lupine plant is considered adequate for sustainable agriculture due to its capacity to fix atmospheric nitrogen in the soil [3] and its suitability for crop rotation, being a good precursory for other plant cultures [4]. However, the nutrient content of lupine seeds and their quality are influenced by the species, cultivars, selected agrotechniques and pedoclimatic factors for plant growth [5].…”
Section: Introductionmentioning
confidence: 99%